Immune alterations and overexpression of CTCF in endometrial carcinoma: insights from molecular subtyping - Wei, Caiping; Chen, Guowei; Chen, Kun; Fang, Shuang; He, Hongying (Cancer cell international, 2024)
Endometrial cancer (EC) is a prevalent epithelial malignancy originating in the female endometrium, and its global incidence has been on the rise over the past decade. Despite significant scientific progress has been achieved recently, the genetic factors underlying EC pathogenesis remain poorly understood, warranting further investigation. We employed transcriptomic datasets from the Genomic Data Commons database to extract variable and clinical data. Quantile normalization and log2 transformations were applied to obtain a gene expression matrix for the sample cohort. Various assays, such as quantitative real-time polymerase chain reaction (qRT-PCR), western blotting, immunohistochemistry (IHC), wound healing assay, transwell assay, and TUNEL assay, were employed in the study to examine the involvement of CTCF in EC cell biology. Additionally, in vivo experiments were conducted using a subcutaneous transplantation tumor model in athymic nude mice. The potential mechanism of action of CTCF was also illustrated by identifying differentially expressed genes (DEGs) and functions after interfering with CTCF gene expression through the GSPAdb online database. After categorizing 543 samples into cohorts with high and low ImmuneScores, we discovered 1025 genes that were differentially expressed, including 745 genes that were up-regulated and 280 genes that were down-regulated in the high scores group compared to the low scores group. Tumor mutation burden (TMB) analysis highlighted 11 genes with the highest mutation frequency. Furthermore, 16 immune checkpoints and 50 immune regulatory factors exhibited differential expression. Among these, CTCF was up-regulated in EC. We found that CTCF knockdown could diminish EC's invasive ability and metastatic potential while enhancing apoptosis. In vivo experiments corroborated that CTCF knockdown could reduce tumor growth. The GSPAdb online database identified differential expression pathways mainly enriched in cellular metabolism as well as some intracellular classical signaling pathways after interfering with CTCF gene expression. In addition, we identified potential downstream regulators of CTCF through protein interaction networks. This study unveiled comprehensive molecular characteristics and DEGs in EC, emphasizing the up-regulation of CTCF in EC. Our findings collectively suggest that CTCF represents a promising therapeutic target, and our gene molecular typing model offers a novel approach for prognostic evaluation in EC.